Modeling DMPC lipid membranes with SIRAH force-field - Barrera Guisasola, Exequiel Ernesto (2017)
Coarse-grained simulation schemes are increasingly gaining popularity in the scientific community because of the significant speed up granted, allowing a considerable expansion of the accessible time and size scales accessible to molecular simulations. However, the number of compatible force fields capable of representing ensembles containing different molecular species (i.e., Protein, DNA, etc) is still limited. Here, we present a set of parameters and simplified representation for lipids compatible with the SIRAH force field for coarse-grained simulations (http://www.sirahff.com). We show that the present model not only achieves a correct reproduction of structural parameters as area per lipid and thickness, but also dynamic descriptors such as diffusion coefficient, order parameters, and proper temperature driven variations. Adding phospholipid membranes to the existing aqueous solution, protein and DNA representations of the SIRAH force field permit considering the most common problems tackled by the biomolecular simulation community.